Comparison between patient-controlled epidural analgesia and continuous epidural infusion for pain relief after gynaecological surgery. - Suhaila N,; Nurlia Y,; Azmil Farid Z,; Melvin K,; Muhammad M,; Nadia MN, (Department of Surgery, UKM Medical Centre, 2013)
This prospective, randomised study compared the effectiveness of patient controlled epidural analgesia (PCEA) versus continuous epidural infusion (CEI) in providing pain relief post gynaecological surgery. Sixty six ASA I or II patients planned for gynaecological surgery via Pfannensteil incision under combined spinal epidural anaesthesia were recruited. They were randomised into two groups: Group A patients received PCEA while Group B patients received CEI. In the recovery area, both groups received an epidural combination of levobupivacaine 0.1% and fentanyl 2 μg/ml. Group A patients were allowed demand bolus doses of 5 ml with a 20 minute lockout interval, while Group B patients had their epidural infusion initiated at 6 ml/hour with increments as required to a maximum of 12 ml/hour. Pain score and degree of motor blockade was assessed hourly in the first four hours and subsequently at four hourly intervals. Side effects were recorded at four-hourly interval. The total amount of analgesia, number of anaesthetic interventions and patient satisfaction was assessed 24 hours, postoperatively. There was no significant difference in pain score, total amount of analgesia, number of anaesthetic interventions and patient satisfaction. The degree of motor blockade and side effects were comparable between the groups. In conclusion, PCEA was comparable to CEI for pain relief after gynaecological surgery.